High‐resolution experiments on chemical oxidation of DNAPL in variable‐aperture fractures. Issue 4 (11th April 2015) - Arshadi, Masoud; Rajaram, Harihar; Detwiler, Russell L.; Jones, Trevor
Abstract: Chemical oxidation of dense nonaqueous‐phase liquids (DNAPLs) by permanganate has emerged as an effective remediation strategy in fractured rock. We present high‐resolution experimental investigations in transparent analog variable‐aperture fractures to improve understanding of chemical oxidation of residual entrapped trichloroethylene (TCE) in fractures. Four experiments were performed with different permanganate concentrations, flow rates, and initial TCE phase geometry. The initial aperture field and evolving entrapped‐phase geometry were quantified for each experiment. The integrated mass transfer rate from the TCE phase for all experiments exhibited three time regimes: an early‐time regime with slower mass transfer rates limited by low specific interfacial area; an intermediate‐time regime with higher mass transfer rates resulting from breakup of large TCE blobs, which greatly increases specific interfacial area; and a late‐time regime with low mass transfer rates due to the deposition of MnO2 precipitates. In two experiments, mass balance analyses suggested that TCE mass removal rates exceeded the maximum upper bound mass removal rates derived by assuming that oxidation and dissolution are the only mechanisms for TCE mass removal. We propose incomplete oxidation by permanganate and TCE solubility enhancement by intermediate reaction products as potential mechanisms to explain this behavior. We also speculate that some intermediate reaction products with surfactant‐like properties may play a role in lowering the TCE‐water interfacial tension, thus causing breakup of large TCE blobs. Our quantitative experimental measurements will be useful in the context of developing accurate computational models for chemical oxidation of TCE in fractures. Key Points: Gradual breakup of large blobs was observed during our oxidation experiments The total mass transfer rate from TCE blobs exhibited three distinct time regimes